2003
DOI: 10.1002/adma.200304539
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystalline In2O3 Nanotubes Filled with In

Abstract: Single‐crystalline In2O3 nanotubes with cubic structure were synthesized via a physical vapor depostion process. The nanotubes grew along the 〈111〉 direction and were continuously filled with metallic In (see Figure). Photoluminescence measurement results displayed strong orange emission. Indium‐filled In2O3 nanotubes represent an exciting system and offer great potential for application in electronic devices or “nanothermometers”.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
155
3
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(165 citation statements)
references
References 16 publications
6
155
3
1
Order By: Relevance
“…A similar phenomenon, associated with the encapsulated In in In 2 O 3 nanotubes under electron irradiation, has been observed. [22] In the present case, the temperature in the vicinity of a junction area increases, Ga entirely melts upon irradiation (bulk Ga has a melting point of 29.8 C, although it may also remain liquid at lower temperatures, when confined within a nanotube shape [20b] ) and thermally expands at a very low basic pressure (~1 10 ±5 Pa) in the TEM chamber. This favors the movement and/or partial evaporation of the Ga part within a silica nanotube; when the beam is removed from the junction area.…”
Section: Methodsmentioning
confidence: 99%
“…A similar phenomenon, associated with the encapsulated In in In 2 O 3 nanotubes under electron irradiation, has been observed. [22] In the present case, the temperature in the vicinity of a junction area increases, Ga entirely melts upon irradiation (bulk Ga has a melting point of 29.8 C, although it may also remain liquid at lower temperatures, when confined within a nanotube shape [20b] ) and thermally expands at a very low basic pressure (~1 10 ±5 Pa) in the TEM chamber. This favors the movement and/or partial evaporation of the Ga part within a silica nanotube; when the beam is removed from the junction area.…”
Section: Methodsmentioning
confidence: 99%
“…The few such NIR OLEDs reported to date have been based on low-bandgap polymers, [9] or polymer±small molecule blends that exploit p-conjugated dyes, [10] or rare-earth-ion [7,8] dopants. Energy gap law effects, [11] as well as the spin-and LaPorte-forbidden nature of the pertinent lanthanide f-manifold transitions, diminish the external electroluminescence (EL) quantum efficiencies of these LEDs (< 0.4 % photons per electron) with respect to analogous devices that emit light in the visible; furthermore, NIR LEDs based on polymer±small molecule blend strategies often suffer from inadequate dopant spectral overlap with the emission band of an optimal host polymer, or limitations that derive from modest number of emission frequencies (e.g., 1540, 1320, 1064, and 977 nm) supported by rare-earth chelates.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Much effort has been made in the past decade toward the study of carbon nanotubes with layered structures. 1,2 Recently, processing of inorganic nanotubes with nonlayered structures received significant interest.…”
Section: Introductionmentioning
confidence: 99%
“…5 Li et al reported the synthesis of In 2 O 3 nanotubes following a liquid metal assisted route. 6 In some cases, nanowires were used as templates for the synthesis of single crystalline inorganic nanotubes. Yang and co-workers synthesized single crystalline GaN nanotubes using ZnO nanowires as templates.…”
Section: Introductionmentioning
confidence: 99%